High altitude endurance training: Effect on aerobic capacity and work performance - Levine, B. D.; Engfred, K.; Friedman, D.; Kjaer, M.; Saltin, B.; Clifford, P. S.; Secher, N. H. (Medicine & Science in Sports & Exercise, 1990)
Living at an altitude of 2500 m and training at 1250 m was shown to improve VO2max, 5000 m run time, and increase blood volume. On the other hand, a group living and training at 1250 m showed no changes in any of these variables. This was proposed as supporting the benefits of "living high and training low." As with many altitude studies, acceptable experimental designs are difficult to implement and control. This investigation suffered a number of shortcomings. 1. The trained participants might not have reached a training plateau prior to going to altitude. Thus, there might have been a training effect demonstrated rather than an altitude effect, or even a combination of the two. Since it has been shown that highly trained athletes experience decrements in VO2max at 2500 m, the demonstration of improved VO2max in this study supports a training effect interpretation. 2. The use of 1250 m as a sea-level equivalent is inappropriate. 3. The living conditions, diets, and emotional settings might have been different for each group. The "special" treatment of the altitude-living group and the daily focus on travel and preparations could have mediated a qualitatively different training response. Implication: It is difficult to accept the findings of this investigation as being sound. It did not control potential confounding factors which is important in studies of this type. Only when sound research is conducted will this hypothesis be evaluated accurately.